Perbedaan Tajam Penglihatan Pascaoperasi Fakoemulsifikasi Pada Pasien Katarak Dengan Diabetes Melitus dan Tanpa Diabetes Melitus - Putu Gede Wirakusuma Putra; Ni Nyoman Sunariasih; Rima Kusuma Ningrum (Aesculapius Medical Journal, 2022)
[The Differences of Visual Acuity After Phacoemulsification Surgery in Cataract Patients With Diabetes Mellitus and Without Diabetes Mellitus] Phacoemulsification surgery in cataract patients with diabetes mellitus is performed to improve visual acuity so as to improve patient’s quality of life. Phacoemulsification is one of the most efficient and widely used surgical techniques. The aim of this study was to determine the visual acuity after phacoemulsification surgery in cataract patients with diabetes mellitus and without diabetes mellitus. This research is an analytic observational with a cross sectional research design that used medical records of Bali Mandara Eye Hospital in 2019. The subjects were 59 cataract patients with diabetes mellitus and 59 cataract patients without diabetes mellitus. The collected data were analyzed by using the Mann Whitney test. The value of p<0.05 was significant. The results showed that cataract patients with diabetes mellitus (44,1%) had moderate visual acuity after phacomulsification surgery. Furthermore, the cataract patients without diabetes mellitus (55,9%) had good visual acuity after phacoemulsification surgery. There was a significant difference between visual acuity after phacoemulsification surgery in cataract patients with diabetes mellitus and without diabetes mellitus as indicated by the p value = 0.049. Cataract patients without diabetes mellitus had better visual acuity after phacoemulsification surgery compared to cataract patients with diabetes mellitus.